Hadith about Religious Pluralism from Imam Syafi'i's Perspective and Its Implementation in Panjunan Bulusidokare Village, Sidoarjo - Darwati, Aan; Muhid, Muhid; Atim Muthoharah, Isnaini Lulu' (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This research examines inter-religious harmony in Panjunan Bulusidokare Village, Sidoarjo, with a focus on tolerance and religious pluralism, as well as the application of Imam Syafi'i's perspective in social and religious contexts. The purpose of this study is to understand the dynamics of tolerance between religious communities, especially in terms of mutual understanding and respect for religious differences, and to identify the principles of pluralism according to Imam Syafi'i that are relevant in the daily lives of people in Panjunan Bulusidokare Village. This research used a qualitative approach with a case study design. Data were collected through in-depth interviews with religious leaders, community leaders, and community members from various religions in the village. Data analysis used a thematic approach to identify patterns and themes related to religious pluralism and tolerance by applying John Hick's theory of pluralism that distinguishes two types of religious experience: the experience of God as a personal and non-personal entity. This study found that religious tolerance in Panjunan Bulusidokare Village is achieved through mutual understanding, respect for differences, and prioritizing the principle of social cooperation between religious communities. In addition, the results show that tolerance in Islam is not only based on religious beliefs but also in the context of protecting non-Muslim rights and inclusive social interactions. The contribution of this research is to enrich the understanding of tolerance and religious pluralism, particularly in the context of rural communities in Indonesia, as well as integrating Imam Syafi'i's perspective within the framework of John Hick's theory of pluralism to promote interfaith harmony. It also provides practical guidance for creating a more harmonious and respectful society amidst religious differences.